Peningkatan Literasi Kesehatan Masyarakat tentang Data Resume Medis Kelurahan Jumputrejo - Djamaludin, Rachmad; Sutha, Diah (Jurnal Pengabdian Kepada Masyarakat, 2025)
Good medical resume data management is one of the important indicators in health services, because the data functions as a concise document that supports medical and administrative decision-making. However, low public health literacy often leads to inaccurate information contained in the data. This community service activity aims to improve public health literacy about medical resume data in Jumputrejo Village, Sukodono District, Sidoarjo Regency. The method used is Community-Based Participatory Research (CBPR) with an action research approach. Case studies are used as an instrument to understand the needs and obstacles of the community regarding filling in medical resume data. This activity was carried out in several stages, including socialization, focus group discussions, simulations, and evaluations through pre-tests and post-tests. The results of the activity showed an increase in public health literacy, marked by an increase in public understanding from 35% before the activity to 82% after the activity. In addition, the community showed active involvement in discussion and simulation sessions, which helped reduce concerns regarding the privacy and security of medical data. This activity also succeeded in encouraging the community to be more aware of the importance of medical resume data in supporting optimal health services. In conclusion, the community-based education approach is effective in improving public health literacy related to medical resume data. Recommendations for the sustainability of this program are the involvement of local health cadres in supporting community education on an ongoing basis.